Diversity and antibacterial activity of endophytic fungi isolated from the medicinal plant of Syzygium jambos - KURRATUL ‘AINI; ELFITA ELFITA; HARY WIDJAJANTI; ARUM SETIAWAN (Society for Indonesian Biodiversity, 2022)
Abstract. ‘Aini K, Elfita, Widjajanti H, Setiawan A. 2022. Diversity and antibacterial activity of endophytic fungi isolated from the medicinal plant of Syzygium jambos. Biodiversitas 23: 2981-2989. Currently, antimicrobial resistance is one of the most important threats to global public health. This is due to the various mechanisms of antimicrobial resistance. Thus, the need for new sources of bioactive compounds outside conventional antibiotics is a top priority. This investigation evaluated the diversity and antibacterial activities of endophytic fungi isolated from the leaves and root bark of jambu mawar (Syzygium jambos (L.) Alston). The endophytic fungi were grown on PDA media, and their antibacterial activities were tested using the Kirby-Bauer method on two Gram-positive and two Gram-negative bacteria. A total of 10 (SJD1-SJD10) and 11 isolates (SJA1-SJA11) of endophytic fungi were identified from the leaves and root bark of S. jambos, respectively. Among them, SJA8 isolate exhibited strong antibacterial activity. Based on morphological characterization and phylogenetic tree analysis, SJA8 was identified as Pleiocarpon livistonae. Isolation and identification of pure compounds from the fungi may reveal potential candidates for new antibiotic substances.